Contrasting the Effects of the 1850–1975 Increase in Sulphate Aerosols from North America and Europe on the Atlantic in the CESM. Issue 21 (7th November 2018) - Undorf, S.; Bollasina, M. A.; Booth, B. B. B.; Hegerl, G. C.
Abstract: The extent and mechanisms of the Atlantic response to the historical (1850–1975) increase of sulphate aerosol emissions from North America and Europe as simulated in eight‐member ensemble experiments with the coupled Community Earth System Model (CESM1)‐Community Atmosphere Model version 5.3 are contrasted. The results show that aerosols from either source cause a long‐term cooling of North Atlantic sea surface temperatures, with the patterns a combination of atmospheric aerosol effects and an aerosol‐induced strengthening of the Atlantic Meridional Overturning Circulation. The response to North American emissions is larger since prevailing winds cause wider aerosol spread over the Atlantic, collocated with climatological cloud cover. The Intertropical Convergence Zone shifts southward affecting tropical precipitation globally. The simulated (multi)decadal components of sea surface temperature and Atlantic Meridional Overturning Circulation variability are furthermore primarily externally forced. The analysis provides novel insights into the mechanisms of aerosol impact on the Atlantic. It suggests that projected further emission reductions will lead to opposite changes. Plain Language Summary: Changes in North Atlantic ocean surface temperatures on time scales of ten or more years impact climate worldwide. However, there is still no consensus on how much of the observed Atlantic variations since the mid‐nineteenth century are due to natural variability or man‐made factors and on the roles of atmosphere, ocean, and their interactions. Here we use a comprehensive global climate model to understand better the effect of man‐made emissions of sulphur dioxide on the Atlantic. This gas forms little particles (aerosols) in the atmosphere, which can influence climate by interacting with sunlight and clouds. We run model simulations for the period 1850–1975 with and without estimates of aerosol emissions from North America and Europe, where most of the global emissions came from. We find that aerosols from both continents caused a decrease in Atlantic temperatures and caused changes in ocean circulation to bring in turn more heat into the North Atlantic. The aerosols caused rainfall over equatorial countries to move southward; this effect was larger for North American than for European emissions. If reality behaves like the model, we expect these changes to reverse when aerosol emissions decrease further in the future, with impacts on ecosystems and livelihoods. Key Points: Anthropogenic sulphate aerosols cause substantial long‐term cooling of North Atlantic SSTs in the coupled CESM1‐CAM5 model during 1850–1975 North American emissions cause more cooling than European emissions due to aerosol and cloud patterns but both share AMOC and ITCZ response External forcing dominates the simulated multidecadal SST (AMV) and AMOC variability, and the forced response is detected in the observed AMV